2021
DOI: 10.1186/s12944-021-01438-4
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein-associated phospholipase A2 levels, endothelial dysfunction and arterial stiffness in patients with stable coronary artery disease

Abstract: Background Lipoprotein-associated Phospholipase A2 (Lp-PLA2), can exert proinflammatory as well as proatherogenic properties on the vascular wall. The current study sought to evaluate the influence of high Lp-PLA2 levels on indices of arterial wall properties in patients with stable coronary artery disease (CAD). Methods Three hundred seventy-four consecutive patients with stable CAD (mean age 61 ± 11 years, 89% males) were enrolled in this single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Circulating LPPLA2 is considered an indicator of inflammation and is associated with vascular dysfunction [ 126 ]. Among patients with stable CAD, a high level of LPPLA2 is associated with endothelial dysfunction and arterial stiffness as an independent risk factor [ 127 ]. In the CoQ10 treated group, the level of LPPLA2 in serum was significantly lower than in the diabetic group using the Rat LPPLA2 ELISA kit.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating LPPLA2 is considered an indicator of inflammation and is associated with vascular dysfunction [ 126 ]. Among patients with stable CAD, a high level of LPPLA2 is associated with endothelial dysfunction and arterial stiffness as an independent risk factor [ 127 ]. In the CoQ10 treated group, the level of LPPLA2 in serum was significantly lower than in the diabetic group using the Rat LPPLA2 ELISA kit.…”
Section: Discussionmentioning
confidence: 99%
“…PLA acetylhydrolase-7 is a member of the lipase family and is responsible for deactivating PLA, an important proinflammatory signaling molecule ( 31 ). Studies investigating the association between plasma levels of PLA acetylhydrolases and cardiovascular disease have found that higher levels of PLA acetylhydrolase-7 lead to an increased risk of cardiovascular disease ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In plasma, LP-PLA2 circulates mainly bound to LDL and is less associated with HDL, which are the other two essential biomarkers for monitoring cardiac and cerebrovascular disorders. Moreover, the dynamics of LP-PLA2 between LDL and HDL have clinical significance, with variations in these two fractions observed in patients with hyperlipidemia and coronary artery diseases [51]. As LP-PLA2 bound to HDL has antiatherogenic properties, while LDL-bound-LP-PLA2 has the opposite effect, the LP-PLA2 molecule has increasingly relevant roles from both pathophysiological and therapeutical points of view.…”
Section: Lipoprotein-associated Phospholipase A2 (Lp-pla2)mentioning
confidence: 99%